HUKUM SESAJEN DALAM PESTA PERNIKAHAN MENURUT PERSPEKTIF HUKUM ISLAM - Wahid Firmansyah; Muhammad Kurniawan Budi Wibowo; B Baehaqi; Meti Fatimah (MAMBA'UL 'ULUM, 2023)
The purpose of this study is to find out the Law of Offerings in Weddings According to the Perspective of Islamic Law. This research is a qualitative research. The subjects of this research are residents of Pagutan Village, Manyaran District, Wonogiri Regency, Central Java Province. Collecting data in this study using observation, interviews and documentation. Then this study uses data analysis, namely data reduction, data presentation and data lever. The results in this study indicate that the customs of the surrounding community are accustomed to the culture of offerings such as the types and functions of offerings such as the offerings of pairs of tarub, offerings of siraman, offerings of midodaren, and finally offerings of Panggih. While the function of the offering itself according to the Javanese community as a form of spiritual negotiation between humans and supernatural powers so that these super natural creatures or essences are not harmful. From the above statement that the tradition of offerings at weddings according to Islamic law is included in the fasid habit. Because it contradicts the verses in the Koran. Therefore, the act of entering into major shirk which is prohibited in Islam can even expel someone from Islam. So, the law of carrying out this ritual of marriage offerings is haram.